Comparative Evaluation of Frictional forces between different Archwire-bracket Combinations - Singh, Vinit; Acharya, Swati; Patnaik, Satyabrata; Nanda, Smruti Bhusan (Orthodontic Journal of Nepal, 2014)
Introduction: During sliding mechanics, frictional resistance is an important counterforce to orthodontic tooth movement; whichmust be controlled to allow application of light continuous forces. Objective: To investigate static and kinetic frictional resistance between three orthodontic brackets: ceramic, self-ligating, andstainless steel, and three 0.019×0.025” archwires: stainless steel, nickel-titanium, titanium-molybdenum. Materials & Method: The in vitro study compared the effects of stainless steel, nickel-titanium, and beta-titanium archwires onfrictional forces of three orthodontic bracket systems: ceramic, self-ligating, and stainless steel brackets. All brackets had 0.022”slots, and the wires were 0.019×0.025”. Friction was evaluated in a simulated half-arch fixed appliance on a testing machine. Thestatic and kinetic friction data were analyzed with 1-way analysis of variance (ANOVA) and post-hoc Duncan multiple rangetest. Result: Self-ligating (Damon) brackets generated significantly lower static and kinetic frictional forces than stainless steel (Gemini)and ceramic brackets (Clarity). Among the archwire materials, Beta-titanium showed the maximum amount of frictional forceand stainless steel archwires had the lowest frictional force. Conclusion: The static and kinetic frictional force for stainless steel bracket was lowest in every combination of wire.